Evaluación técnico- financiera de la implementación de las mallas piramidales en el sistema de control de sólidos primario durante la perforación de un pozo en la sección 12 ¼” en el campo Castilla (2018)
In the present work of degree a technical and financial evaluation of the implementation of pyramidal meshes in the equipment of control of solids for the perforation of the stretch 12 ¼ "of the well Castilla 416, in the Field Castilla, located specifically to the Southwest of the Basin of the Eastern Plains To carry out the evaluation, the geological generalities of the field, such as history, location, stratigraphy, petroleum geology and production history, general characteristics and characteristics of the field, primary equipment and the meshes used were studied. For the analysis of the behavior of the meshes, planes that currently use the perforation of the field and the pyramidal meshes that can be implemented, three field and laboratory tests were carried out, which were the cuttings moisture, the density of the drilling fluid and elimination of solids, in order to technically compare both meshes, according to the size of the operation.